2010
DOI: 10.1038/labinvest.2010.112
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated progression of diet-induced steatohepatitis in glutathione-deficient mice

Abstract: In nonalcoholic fatty liver disease (NAFLD), depletion of hepatic antioxidants may contribute to the progression of steatosis to nonalcoholic steatohepatitis (NASH) by increasing oxidative stress that produces lipid peroxidation, inflammation, and fibrosis. We investigated whether depletion of glutathione (GSH) increases NASH-associated hepatic pathology in mice fed a diet deficient in methionine and choline (MCD diet). Wild-type (wt) mice and genetically GSH-deficient mice lacking the modifier subunit of glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 47 publications
8
56
2
Order By: Relevance
“…No ballooning, a feature of steatohepatitis, was noted in any of the livers. The nonalcoholic fatty liver disease scores we obtained in the control Gclm −/− and Gclm +/+ mice in the present study are very similar to those reported for control Gclm −/− and Gclm +/+ mice in another recent study (Haque et al, 2010). Table 3 Effects of prenatal BaP exposure and Gclm genotype on hepatic nonalcoholic fatty liver disease (NAFLD) scores (estimated marginal means ± SEM).…”
Section: Effects Of Prenatal Bap Exposure and Gclm Genotype On Adipossupporting
confidence: 89%
See 1 more Smart Citation
“…No ballooning, a feature of steatohepatitis, was noted in any of the livers. The nonalcoholic fatty liver disease scores we obtained in the control Gclm −/− and Gclm +/+ mice in the present study are very similar to those reported for control Gclm −/− and Gclm +/+ mice in another recent study (Haque et al, 2010). Table 3 Effects of prenatal BaP exposure and Gclm genotype on hepatic nonalcoholic fatty liver disease (NAFLD) scores (estimated marginal means ± SEM).…”
Section: Effects Of Prenatal Bap Exposure and Gclm Genotype On Adipossupporting
confidence: 89%
“…Our previous studies showed that Gclm −/− mice are more sensitive to the gonadal toxicity of gestational exposure to BaP than wild type littermates (Lim et al, 2013;Nakamura et al, 2012) and that female Gclm −/− mice are subfertile (Nakamura et al, 2011). In contrast, Gclm null mice are protected against diet-induced steatohepatitis, showing upregulation of hepatic antioxidant genes and downregulation of triglyceride synthesis and fatty acid ␤-oxidation (Haque et al, 2010;Kendig et al, 2011). Nonalcoholic hepatic steatosis, also called nonalcoholic fatty liver disease, is an independent risk factor for Type 2 diabetes and is prevalent in individuals with metabolic syndrome (Sung and Kim, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…28,40 Furthermore, lipid peroxidation, as the main second hit of the two-hit hypothesis, contributes to the pathogenic transition from steatosis to NASH by activating hepatic macrophages to trigger inflammation and inducing hepatocyte injury. 8,41 Therefore, the hepatic injury observed in the HFD-fed mice is considered to be at least partly attributable to elevated oxidative lipids (Figures 1b and c, and 3a). Although 23 weeks of treatment with HFD failed to increase hepatic recruitment of inflammatory cells in the mice, elevated TNF-a gene expression was detected in their livers, showing a trend toward the Th-1 polarized inflammatory response (Figures 2a, and 4a and c-f, and Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic steatosis induced by lipid accumulation in hepatocytes is recognized as the first hit, 7,8 and is also identified as a critical prerequisite for the development of inflammation and an independent risk factor for liver fibrosis. 9,10 The second hits are presumably considered to contribute to the progression from simple steatosis to steatohepatitis.…”
mentioning
confidence: 99%
“…In NASH, the fatty acid overload plays an important role in ROS generation as a result of electron leakage during mitochondrial β-oxidation in energy production (Haque et al, 2010). Levels of CPT-1, a ratelimiting regulator of mitochondrial β-oxidation through its role in mitochondrial fatty acid import, were increased in the steatosis model mice, whereas administration of TAM significantly decreased CPT-1 levels compared to the TAM-unadministered mice.…”
mentioning
confidence: 96%